Greek art : from Oxford to Portugal and back again - Morais, Rui (Archaeopress archaeology., 2017)
One of the most fascinating topics in the study of ancient art concerns artistic practices and models and the means of transmission of iconographic designs and decorative compositions. This phenomenon, although well known, has not drawn much attention of scholars of the ancient art. Apart from copies of originals, the practice dates back to the first civilizations and may be even older. The media used could be painted vignettes on papyri, paint on leather, or sketches painted on ostraca, used as pattern books. This issue is practically unheard of regarding ancient Greece, although a few media have been found which may have facilitated the transmission of iconographic designs and decorative compositions. In this study we present some examples that suggest the existence of pattern books in the Greek world.